Stepfamily Relationships - Ganong, Lawrence H. author. aut Link
Approx. 400 p.
Keywords: Stepfamily Relationships: Development, Dynamics, and Interventions offers what has so far been missing in the field - a comprehensive, multidisciplinary text that provides a state-of-the-art look at this important facet of family study. This volume examines the variety of relationships within step-households as well as between households, focusing on internal family dynamics while maintaining a cultural and historical viewpoint. The diversity and complexity of families is emphasized throughout, including gay and lesbian stepfamilies, stepfamilies of varying racial and ethnic backgrounds, and stepfamilies across the life course. It will be a welcome text and reference for all those who study and work with stepfamilies and families in general.